Altered Cerebro-Cerebellar Limbic Network in AD Spectrum: A Resting-State fMRI Study - Qi, Zhigang; An, Yanhong; Zhang, Mo; Li, Hui-Jie; Lu, Jie (Frontiers in Neural Circuits, 2019)
Recent evidence suggests that the cerebellum contributes not only to motor but also to non-motor cognitive functions, and that several coupled cerebro-cerebellar networks exist, including links with the limbic network. Since several limbic structures are affected by Alzheimer pathology, even in the preclinical stages of Alzheimer's disease (AD), we wanted to evaluate the pattern of activity in the cerebral limbic network from the perspective of the cerebellum. Twenty patients with mild cognitive impairment (MCI), 18 patients with AD, and 26 healthy controls (HC) were recruited to acquire resting-state functional magnetic resonance imaging. A seed-based method was applied to construct a cerebellar-cerebral limbic network by using a predefined seed cerebellar region of interest. Two-sample t-tests were performed to detect significant changes in the cerebellar limbic network connectivity between each pair of the three groups. The first result, a sub-scale network including the bilateral posterior part of the orbitofrontal cortex extending to the anterior insular cortex and left inferior parietal lobule, showed greater functional connectivity in patients with MCI than in HC and less functional connectivity in patients with AD than in MCI. The location of this sub-scale network was in accordance with components of the ventral attention network. Second, there was decreased functional connectivity to the right mid-cingulate cortex in the AD and MCI patient groups relative to the HC group. As the cerebellum is not compromised by Alzheimer pathology in the early stages of AD, this pattern indicates that the sub-scale ventral attention network may play a pivotal role in functional compensation through the coupled cerebro-cerebellar limbic network in MCI, and the cerebellum may be a key node in the modulation of social cognition.